The Effect Of Corporate Social Responsibility & Good Corporate Gorvernance On Company Value On Manufacturing Companies Listed On IDX For The 2016 – 2020 Period - Aa Kartiwa; Felicia Rizky Muhammad (Universitas Sebelas April, Fakultas Ekonomi dan Bisnis, 2023)
This study aims to examine the effect of corporate social responsibility and good corporate governance as a proxy for managerial ownership on firm value in manufacturing companies. The population in this study were all manufacturing companies listed on the Indonesia Stock Exchange (IDX). The samples taken were manufacturing companies listed on the Indonesia Stock Exchange during the period 2016 to 2020. The total research sample was 6 manufacturing companies determined through purposive sampling. The analytical method of this study uses multiple regression analysis techniques. The results of this study indicate that corporate social responsibility has no effect on firm value. Good corporate governance has no significant effect on firm value.